Through Infrastructure: Pneumatic Transport and the Continuity of the Technical Fix from the Nineteenth to the Twenty-first Century - Laura Meneghello (Global Environment)
Since the beginning of the twenty-first century, pneumatic tube-based transport has been depicted as a ‘green’, ‘sustainable’ infrastructure for the transport of both people and goods; it has been represented as a possible solution to help reduce traffic congestion, air pollution and carbon-dioxide emissions and as an alternative to heavy transport. In fact, air pollution occupies a crucial position in the hierarchy of urban problems. The article analyses sustainability discourses related with nineteenth-century atmospheric railways and similar air-driven transport solutions up to the present day, showing how techno-scientific plans and utopian representations put forward the idea that environmental problems could be solved through technology. In particular, in the twenty-first century, Hyperloop has been presented as an answer to climate and environmental crises, whereas contemporary discourses of clean transport tend to reproduce nineteenth-century discourses on the purity of air granted by the atmospheric railway.